The storyteller - Hobson, Brandon (Scholastic Press, 2023)
Ziggy's mother disappeared ten years ago, one of the many Native women who have mysteriously gone missing, and Ziggy believes a secret cave may hold the key--so with his sister, Moon, and friends Alice and Corso, he sets out to find the cave and solve the mystery of his family's origins.